Resident attitudes towards support for future tourism: utilising the Social Exchange Theory (SET)/ Irfana Rashid - Rashid, Irfana (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2020)
The purpose of this article is to present a model that expresses a relationship between the local resident's perception towards developmental tourism impacts (economic, environmental and social) and their support for future tourism development. The research instrument measures the environmental, economic and social impacts and assesses the respondents' support for future tourism development. The data was collected from the local residents of different districts in Kashmir Valley. A total of 316 valid questionnaires were analyzed using AMOS-24. The results indicated that the rural residents' perception of tourism development does have an impact on their support for tourism development. The findings also showed that gender and the geographical area does moderate the relationship between their perception of tourism development impacts and their support for future tourism development.